New molecular complex of ammonium glycyrrhizate with rutin - L. A. Yakovishin; V. D. Ratnikov; P. I. Bazhan; G. P. Zaitsev (Chimica Techno Acta)
A new 1:1 molecular complex of triterpene glycoside ammonium glycyrrhizate (GC) with flavonoid glycoside rutin (Rut) was obtained in aqueous ethanol. The stability constant (9.7±0.2)×104 (mol/L)–1 was calculated for the complex via isomolar curves. The complexation was studied by UV- and ATR IR-Fourier spectroscopy and a method of isomolar series. The hydrogen bonds and hydrophobic interactions are formed in the molecular complex. A preliminary antioxidant activity assessment of the complex was made.